Microbial infection and antibiotic patterns among intensive care unit patients in a tertiary hospital in Central Nepal - Sanjana, RK; Majhi, PC (Journal of College of Medical Sciences-Nepal, 2013)
Aims The present study is a fundamental effort to evaluate the bacteriological and antibiotic patterns in the Intensive Care Unit (ICU) setting in a tertiary care hospital. This study was carried out to guide the clinician in choosing the appropriate antibiotics and to prevent emergence of multidrug resistance bacteria. Materials and Methods Between March 2009 to Feb 2012, the samples from various ICUs that were submitted to the microbiology laboratory for culture and sensitivity were included in this study. All the organisms were identified morphologically and biochemically by standard laboratory procedure and antibiotic susceptibility pattern was determined by disc diffusion methods. Result Of 3,780 specimens, 2,312 (61.1%) isolates were recovered. Single organisms were isolated from 1,746 (75.5%) samples while the remaining 566 (24.4%) had two or more organisms isolated. Pseudomonas aeruginosa was the most common isolate 819 (35.4%), followed by Klebsiella pneumoniae 637 (27.5%). Antibiotics sensitivity of Pseudomonas aeruginosa showed that almost all isolates were resistant to cephalexin (97.8%) and ciprofloxacin (80.3%). However (95.8%) of the isolates were sensitive to tobramycin, (92.0%) to meropenem & (74.80 %) to amikacin. Conclusion It is concluded that Pseudomonas aeruginosa is the predominate pathogen isolated from ICUs of this Hospital. Most of the frequently isolated pathogens are resistant to cephalosporins and quinolone antibiotics as compared to aminoglycosides and carbapenem. Regular surveillance of antibiotic susceptibility pattern is very important for setting a guideline to the clinician in choosing an appropriate therapy of infected patients of ICUs. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-3, 1-8 DOI: http://dx.doi.org/10.3126/jcmsn.v8i3.8678